From a Vital Sign to Vitality: Selling Exercise So Patients Want to Buy It. Issue 4 (July 2016) - Segar, Michelle L.; Guérin, Eva; Phillips, Edward; Fortier, Michelle
Abstract : Exercise is Medicine ® (EIM) and physical activity as a vital sign are based on health-focused research and reflect ideal frames and messages for clinicians. However, they are nonoptimal for patients because they do not address what drives patients' decision-making and motivation. With the growing national emphasis on patient-centered and value-based care, it is the perfect time for EIM to evolve and advance a second-level consumer-oriented exercise prescription and communication strategy. Through research on decision-making, motivation, consumer behavior, and meaningful goal pursuit, this article features six evidence-based issues to help clinicians make physical activity more relevant and compelling for patients to sustain in ways that concurrently support patient-centered care. Physical activity prescriptions and counseling can evolve to reflect affective and behavioral science and sell exercise so patients want to buy it.